Psychological symptom complex of frustrational behavior of servicemen: gender aspect - Mushkevych, Valentyn (Psychological Prospects Journal, 2021)
Goal. The article examines and analyzes the gender features of frustrational behavior of servicemen of different sexes, presents their empirical justification, presents the procedure and methods of research of frustrational behavior of servicemen, highlights the main psychological features of frustrational behavior of servicemen of different sexes. Methods. Methods of mathematical statistics and psychodiagnostics are used: methods of diagnosing the level of social frustration of L. Wasserman, studying frustration reactions of S. Rosenzweig, self-assessment of mental states of G. Eisenko, aggression of E. Wagner, indicators and forms of aggression of A. Bass and A. Darki, level of emotional burnout V. Boyko. Results. It is noted that in comparison with men, the female part of the military has a significantly higher degree of dissatisfaction with social achievements. It was found that a significantly higher degree of aggression is demonstrated by male subjects. It is proved that in comparison with men, the female part of the military has a significantly higher degree of expression of such indicators as "experiencing traumatic circumstances", "expanding the scope of saving emotions", "self-dissatisfaction". Compared with women, the male part of the subjects has a significantly higher degree of severity of such symptoms of emotional burnout as "emotional deficit", "personal alienation", "reduction of professional responsibilities", "emotional alienation", "psychosomatic and psychovegetative disorders", " inadequate selective emotional response. Conclusions. The presented indicators of the severity of psychological features of frustrational behavior of servicemen of different sexes are included in the perspective of further research, which will be aimed at psychodiagnostic and psychoeducational processes concerning the study servicemen’s ideas about psychological health and healthy lifestyle, to identify motives and stereotypes that are directed towardspreserving and improving the psychological health of servicemen of different sexes with different levels of both objective and subjective vision of the quality of professional functioning.